Nanotechnology Characterization Tools for Tissue Engineering and Medical Therapy - Kumar, Challa S.S.R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2019)
Ninth volume of a 40 volume series on nanoscience and nanotechnology, edited by the renowned scientist Challa S.S.R. Kumar. This handbook gives a comprehensive overview about Nanotechnology Characterization Tools for Tissue Engineering and Medical Therapy. Modern applications and state-of-the-art techniques are covered and make this volume an essential reading for research scientists in academia and industry.
Nanotechnology-Based Stem Cell Tissue Engineering with a Focus on Regeneration of Cardiovascular Systems -- Characterization Tools for Mechanical Probing of Biomimetic Materials -- Open-Channel Separation Techniques for the Characterization of Nanomaterials and Their Bioconjugates for Drug Delivery Applications -- Using Integrated Cancer-on-Chip Platforms to Emulate and Probe Various Cancer Models -- Design of Nanoparticles for Focused Ultrasound Drug Delivery -- Magneto-Responsive Nanomaterials for Medical Therapy in Preclinical and Clinical Settings -- Superparamagnetic Nanoparticles for Cancer Hyperthermia Treatment -- Quantitative Methods for Investigating Dissociation of Fluorescently Labeled Lipid from Drug Delivery Liposomes -- Integrated Multilayer Microfluidic Platforms with Silicon Architectures for Next Generation Health Diagnostic Systems -- Characterization of ATP Nanoliposome Treatment for Regeneration of Injured Spinal Cord -- An Insight into Characterizations and Applications ofNanoparticulate Targeted Drug Delivery Systems.
Keywords: Nanotechnology; Nanochemistry; Nanoscience; Nanotechnology; Nanochemistry; Nanophysics